2021
DOI: 10.1167/iovs.62.13.21
|View full text |Cite
|
Sign up to set email alerts
|

A Hypothalamic-Controlled Neural Reflex Promotes Corneal Inflammation

Abstract: Purpose To test whether an acute corneal injury activates a proinflammatory reflex, involving corneal sensory nerves expressing substance P (SP), the hypothalamus, and the sympathetic nervous system. Methods C57BL6/N (wild-type [WT]) and SP-depleted B6.Cg-Tac1tm1Bbm/J (TAC1-KO) mice underwent bilateral corneal alkali burn. One group of WT mice received oxybuprocaine before alkali burn. One hour later, hypothalamic neuronal activity was assessed in vivo by magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…In animal models of bacterial keratitis (Pseudomonas aeruginosa), SP causes an elevation of levels of pro-inflammatory cytokines (Foldenauer et al, 2012;McClellan et al, 2008), and application of a SP antagonist improves disease outcomes (Hazlett et al, 2007). Excessive release of SP may further promote leukocyte infiltration and delay the apoptosis of neutrophils, leading to neurogenic inflammation (Lasagni Vitar et al, 2022;Zhou et al, 2008). In addition, SP is also reported to promote inflammatory corneal neovascularisation, with increased infiltration of CD45 + leukocytes in mouse corneas after total de-epithelisation, alkali burn, or intrastromal sutures (Barbariga et al, 2018).…”
Section: Corneal Innervation Anatomy and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models of bacterial keratitis (Pseudomonas aeruginosa), SP causes an elevation of levels of pro-inflammatory cytokines (Foldenauer et al, 2012;McClellan et al, 2008), and application of a SP antagonist improves disease outcomes (Hazlett et al, 2007). Excessive release of SP may further promote leukocyte infiltration and delay the apoptosis of neutrophils, leading to neurogenic inflammation (Lasagni Vitar et al, 2022;Zhou et al, 2008). In addition, SP is also reported to promote inflammatory corneal neovascularisation, with increased infiltration of CD45 + leukocytes in mouse corneas after total de-epithelisation, alkali burn, or intrastromal sutures (Barbariga et al, 2018).…”
Section: Corneal Innervation Anatomy and Functionmentioning
confidence: 99%
“…Neurogenic inflammation in the cornea provides evidence for corneal neuroimmune crosstalk. Corneal nerve damage induces immune responses to promote the clearance of disrupted axons, and release of neurotrophic factors that trigger inflammation (Lasagni Vitar et al, 2022). The inflammatory response, including activation of immune cells and released cytokines, can further induce nerve damage, to propogate the corneal neuroinflammation (Launay et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“… 25 More recently, we also showed that following chemical damage of the ocular surface, mice that are genetically unable to express SP showed reduced lymphocyte infiltration and inflammatory response compared to wild-type mice. 58 Finally, we previously observed that topical administration of NK1R antagonist fosaprepitant reduced corneal epithelial disease and inflammation in a murine model of graft-versus-host disease. 59 Others have reported the analgesic potential of NK1 receptor antagonist administration in murine models of acute pancreatitis, 60 interstitial cystitis, 61 and chronic pain.…”
Section: Discussionmentioning
confidence: 96%
“…Recent investigations have revealed that nerve reflexes, orchestrated by the hypothalamus, contribute to corneal inflammation. 23 DRD1, being a prevalent neuroreceptor, likely plays a role in the inflammatory feedback loop within the central axis in the context of corneal injury. Delving into these intricate mechanisms holds promise for future explorations within the realm of corneal injury research.…”
Section: Discussionmentioning
confidence: 99%